Онтоморфогенез рослин видів роду Astragalus L. за інтродукції в Правобережному Лісостепу України - Bondarchuk, O.P.; Rakhmetov, D.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
Purpose – to establish of ontomorphogenesis peculiarities of species of the genus Astragalus L. for the first, second and subsequent years of their life in conditions of introduction into the Right-Bank of Forest-Steppe of Ukraine. Material and methods. Subject of investigation – 19 perennial species of the genus Astragalus. Investigations were conducted in 2012–2015 years on introduction plot of department of new crops of M.M. Gryshko National Botanical Garden of the NAS of Ukraine. The study of life forms of species were carried out as described in I.G. Serebryakov and T.I. Serebryakova. Developmental state allocated according to descriptions of methodology ontogenesis of T.A. Rabotnov and O.V. Smirnova. Results. Peculiarities of ontomorphogenesis of polycarpic perennials plants A. galegiformis L., А. membranaceus (Fisch) Bunge., A. australis (L.) Lam., A. danicus Retz., A. сicer L., A. glycyphyllos L., A. dasyanthus Pall., A. exscapus L., A. tanaiticus K. Koch., A. buchtormensis Pall., A. ponticus Pall. A. arenarius L., A. sulcatus L., A. austriacus Jacq., A. monspessulanus L., A. onobrychis L., A. cornutus (Pall.) Kuntze, A. albicaulis DC., A. falcatus Lam., in conditions of introduction in the Right-Bank of Forest-Steppe of Ukraine are established. Conclusions. It was found that introduced plants of the genus Astragalus species in conditions of culture have four age periods and 10 developmental states: seeds, sprouts, juvenile, immature, virginal, generative, subsenilny and se nile. The duration of ontogeny – about 25 years.